PERKEMBANGAN PENGELOLAAN PERIKANAN GLOBAL - Martosubroto, Purwito (Indonesian Journal of International Law, 2021)
Global fisheries production has been marked by the fast growing pattern of capture fisheries production. During the last five decades marine fisheries production demonstrated an increase of nearly 500% or an annual average increase of 4.5%. this spectacular increase raised a global concern since it accompanied by overexploitation of resources in various parts of the world ocean. This concern has led to a series of negotiation in international arena that resulted in the formulation and finally adaption of the Code of Conduct for Responsible Fisheries in FAO in 1995. Elaboration of the implementation of the Code brought about the formulation of International Plan of Action (IPOA) burning issues of priority for which member countries of FAO are encouraged to translate it into National Plan of Action (NPOA). Four NPOA has been available including IPOA for sharks, for seabird bycatch in longline fisheries, for fishing capacity and for IUU fishing. Regional Fisheries Organization (RFO) in recent years has tasked to deal with management of living resources that do not respect administrative boundaries, such as some species of tuna and small pelages. Some of the fish resources exploited by the Indonesian fishers move across EEZ into high seas for which it falls within the responsibility of regional fisheries organization to manage. Indonesia is therefore encouraged to join such RFO to assure active participation in the management of the resources. Nonetheless, the administrative bureaucracy has hindred the process.